A Causal Model of Instructional Leadership in Digital Era, School Climate, Teacher Competency, Affecting Quality of Future Learners Under the Secondary Educational Service Area Offices - Deelee, Panida; ภูติอริยวัฒน์, จันทรัศม์; พัฒผล, มารุต (The Journal of Development Administration Research, 2025)
This Article aimed to study (1) to develop a causal model of instructional leadership in digital era, school climate and teacher competency affecting quality of future learners under the Secondary Educational Service Area Offices; and (2) to examine the goodness of fit between the proposed model and empirical data. The sample was 320 secondary schools under the Secondary Educational Service Area Offices in the 2024 academic year. Two informants from each school, the school administrator and the head of academic affairs, participated in the study. Schools were selected using multistage random sampling. The research instruments included an expert-informed connoisseurship recording form and a five-point Likert scale questionnaire. Data were analyzed using Structural Equation Modeling (SEM). The research results were found as follows; 1. Instructional leadership in digital era (IL) had a significant direct effect on quality of future learners (QL), and an indirect effect through school climate (SC) and teacher competency (TC), with the highest total effect (Beta = 0.97). Teacher competency (TC) had the strongest direct effect on learner quality (Beta = 0.47), while school climate (SC) significantly influenced teacher competency (TC) (Beta = 0.57) at the statistical level of p < .001. The model accounted for 46% of the variance in future learner quality (R² = 0.46). The model showed a good fit with the empirical data (Chi-Square/df = 1.84, SRMR = 0.04, RMSEA = 0.05, GFI = 0.94, AGFI = 0.93, CFI = 0.91, and TLI = 0.91).